Characterization, Delignification And Hydrolysis Of Malaysia Switchgrass For Sugar Extraction - Wai, Weng Sin (Universiti Sains Malaysia, 2017)
Lignocellulose-to-ethanol conversion is a promising technology to supplement the first generation biofuels and fossil fuels. However, the recalcitrant structure of the lignocellulosic biomass is a major challenge to the efficient conversion of the biomass. To improve and increase the enzymatic digestibility of switchgrass as a lignocellulosic biomass for fermentable sugar or reducing sugar production in hydrolysis, comparison of acid and alkaline pre-treatment using sulphuric acid and sodium hydroxide of the biomass feedstock was investigated. At the condition of 1M concentration, 0.1g/mL pulp density, at standard room and temperature, the biomass was pre-treated respectively at 1, 2, 3, 4 and 5 hours of residence time. Pre-treatment was evaluated based of the weight loss of the treated samples. Both of the pre-treatment achieved the stagnant weight loss at the 4 hours residence time, which were 26% and 26.9% respectively. Then, the research was carried out further to investigate the optimum conditions for the alkaline pre-treatment. The biomass was treated at 4 hours residence time, 0.1g/mL, at standard room temperature and pressure with different concentration varying from 1 to 5M. The highest weight loss was recorded at 28.5% at the 2M NaOH pre-treatment. Pulp density had limited effect on the weight loss at constant residence time and concentration at room temperature and pressure. SEM studies on the pre-treated samples showed a great deal of structural change in the NaOH pre-treated samples and a little or no physical changes on the acid pre-treated samples.